Modelling and Statistical Optimization of Dilute Acid Hydrolysis of Corn Stover Using Response Surface Methodology - Amenaghawon, Andrew Nosakhare (Journal of Science and Technology, 2014)
Response surface methodology (RSM) was employed for the analysis of the simultaneous effect of acid concentration, pretreatment time and temperature on the total reducing sugar concentration obtained during acid hydrolysis of corn stover. A three-variable, three-level Box-Behnken design (BBD) was used to develop a statistical model for the optimization of the process variables. The optimal hydrolysis conditions that resulted in the maximum total reducing sugar concentration were acid concentration; 1.72 % (w/w), temperature; 169.260C and pretreatment time; 48.73 minutes. Under these conditions, the total reducing sugar concentration was obtained to be 23.41g/L. Validation of the model indicated no difference between predicted and observed values.